Factors Affecting User Satisfaction of Local Van (Songthaew): A Case Study of The Local Van (Songthaew) Route 1263 In Pattanakarn Road Soi 20, Bangkok - Chaturaphak Wichian; Jumrus Pitaksringkarn (Engineering and Technology Horizons, 2024)
The research aims to identify the factors affecting satisfaction and suggestions from users of local van (songthaew) route 1263. This will propose measures to manage the operations and improve level of satisfaction. The researcher has established a set of questionnaires for 400 random respondents and using Multiple Regression Analysis to determine the correlation between factors that affect satisfaction. Discover correlations between factors influencing satisfaction using Pearson Product Moment Correlation Coefficient. It was found that factors affecting user satisfaction of local van (songthaew) route 1263 in Pattanakarn road soi 20 by the average satisfaction score of the factors that affect satisfaction (Y1) would be management (X1), physical aspects of vehicles (X2), service (X3), safety (X4) and environment (X5). The equation of predicting satisfaction is Y1 = -2.164E-15 + 0.148 X1 + 0.333 X2 + 0.259 X3 + 0.148 X4 + 0.111X5 The variables can predict the overall satisfaction (Y1) with adjusted R-Square all four factors have equivalent to 1.000 for accuracy (100.0%), the relationship between variables is equal to 1.000. The above equation shows the overall satisfaction across all with an average predictive value (Predicted Y1) of 3.28 (moderate satisfaction). There is a correlation (Pearson Correlation) among there five factors and their satisfaction in the order of the relationship as follow: service (r = 0.764), safety (r = 0.739), environment (r = 0.638), physical aspects of vehicles (r = 0.236) and management (r = 0.058) a significant relationship except for management. The top three additional suggestions from users are installation of GPS systems on the local van (songthaew) route 1263 for convenient passenger tracking (23.0%), decreasing the running time (15.5%), and repairing damaged seats (14.5%). Prioritizing the bus operations management and safety regulations must be established by relevant governmental agencies to promote customer satisfaction. Vehicle examinations must strictly adhere to substantial practices. Operators should receive training on safe driving and outstanding service to boost passenger confidence and service. User suggestions regarding the management are, for example, an appropriate schedule and bus operation punctuality. There should be collaboration between government agencies and the private sector in order to accommodate passengers on main public transportation while connecting with local ones. A public hearing among stakeholders from both the private and governmental sectors should be held in order to gain ideas for improvement, such as fare promotion. Customer satisfaction will be improved if the above measures, along with all other recommendations, are taken into serious consideration by the operator and government agencies.
Keywords: Urban Transport Systems Analysis; Transportation Planning and Optimization